POWER AND LOVE IN KHALED HOSSEINI’S AND THE MOUNTAINS ECHOED - DIAH HAYUSULISTYO W (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
POWER AND LOVE IN KHALED HOSSEINI’S AND THE MOUNTAINS ECHOED Diah Hayusulistyo Wardani English Literature Study Program, Faculty of Languages and Arts, Surabaya State University diahwardani2@gmail.com Prof. Dr. FD Kurnia, M.pd. English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Abstrak Naskah ini berkenaan dengan cinta dan kekuatan yang digambarkan secara berbeda pada tiap jenis cinta yang terjadi antara karakter-karakter pada And The Mountains Echoed, Baba Ayub, Qais, Abdullah, Pari Wahdati, Markos Varvaris, Nabi, Pari Abdullah, dan Nila Wahdati. Cinta dan kekuatan telah menjadi topic utama novel ini sejak di terbitkan pada tahum 2013. Karenanya pembelajaran ini focus pada dua masalah utama, (1) Apa jenis-jenis cinta yang digambarkan pada Khaled Hosseini novel And The Mountains Echoed, dan (2) Bagaimana cinta dan kekuatan digambarkan pada Khaled Hosseini novel And The Mountains Echoed. Data- data pada skripsi ini diambil dari novel yang menjadi sumber data utama dan membaca intensif untuk langkah analisa selanjutnya. Terdapat tiga konsep utama yang akan digunakan, pertama adalah teori umum tentang cinta oleh Thomas Lewis, Fari Amini, dan Richard Lanon, kedua yakni jenis-jenis cinta oleh C.S Lewis, dan yang ketigaadalah konsep cinta dan kekuatan oleh Adam Khane. Untuk menjawab masalah yang pertama, pembelajaran ini menggunakan konsep jenis-jenis cinta yang digambarkan oleh karakter-karakter pada novel. Kemudian masalah kedua dijawab dengan konsep dari cinta dan kekuatan oleh Khane dan mencaritau perbedaan penggambaran cinta dan kekuatan pada tiap jenis-jenis cinta. Selain itu, skripsi ini menggunakan kajian pustaka, analisis dan deskripsi. Kajian pustakadigunakan untuk mengumpulkan data yang diperlukan. Analisa digunakan untuk menganalisa data yang telah didapat berdasarkan teori teori. Deskripsi digunakan untuk mendeskripsikan hasil analisa. Setelah melalui analisa panjang dengan menggunakan tiga macam metode diatas, hal ini dapat mengungkapkan penggambaran dari jenis-jenis cinta bahwa Kasih Sayang digambarkan anatara Baba Ayub dan Qais, Abdullah and Pari Wahdati, dan atara Shuja(seekor anjing) dan Pari; Pertemanan digambarkan antara Markos dan Nabi, dan atara Pari Wahdati dan Pari Abdulah; Percintaan digambarkan antara Nabi dan Nila Wahdati; Derma digambarkan oleh Markos Varvaris. Cinta dan kekuatan digambarkan pada tiap jenis-jenis cinta dengan caranya masing-masing.menyatukan atau dengan sengaja menjauhkan dua orang, menuturkan sejarah kehidupan, saling melengkapi dan berjalan beriringan sty sama lain. Katakunci: Cinta, jenis-jenis cinta, cinta dan kekutan Abstract This paper deals with power and love that depicted in different way by each kinds of love that happened between characters of And The Mountains Echoed, Baba Ayub, Qais, Abdullah, Pari Wahdati, MarkosVarvaris, Nabi, Pari Abdullah, and NilaWahdati. Love and power has become the main topic of this novel since it was published in 2013. Thus this study focuses on two major problems, (1) What kinds of love are depicted in KhaledHosseini’s AndThe Mountains Echoed, and (2) How are power and love depicted in KhaledHosseini’sAnd The Mountains Echoed. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. There are three main concepts that will be used, first is the general theory of love by Thomas Lewis, FariAmini, and Richard Lannon, second is kinds of love by C.S Lewis, and the third is the concept of power and love by Adam Khane. To answer the first problems, this study are using the concept of kinds of love that depicted by the characters in the novel. Then the second problems are answered by the concept of power and love by Khane and find out the different depiction of power and love in each kinds of love. Moreover, this thesis used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it can reveal the depiction of kinds of love that Affection depicted between Baba Ayub and Qais, Abdullah and Pari, and between Pari and Shuja (a dog); Friendship depicted between Markos and Nabi, and between PariWahdati and Pari Abdullah; Eros depicted between Nabi and NilaWahdati; and Charity, depicted by MarkosVarvaris. Power and love depict by each kinds of love in their own way, unites or intentionally spares the two people, resembles the history of life, complete and walks together side by side. Keywords: Love ;Kinds of Love; Power and love. INTRODUCTION Love is an interesting topic to be discussed. In fact, when we do search in Google about love, we can find that there are 5,930,000,000 posting discuss love. Thomas Lewis, Fari Amini, and Richard Lannon in their book titled A General Theory of Love explain that love can deliver us to understand our self, and it can also shape our personality. From the beginning till the end of human life, love is not merely centered to the activity we have but also to the life power of the mind, decide our feelings, balancing the bodily rhythms, and reconstruct our brain arrangement. Our identities is fixed and determined by relationship that guaranteed by the body’s physiology (2000, p. viii). We can find love in much kind of literary works. Love has always been a favorite topic for poets, novelist and songwriters. It has always relationship with literature. And it is difficult to imagine literature without love. Love becomes so universal theme because of the remarkable variety of its world. Nothing else unite human being so emphatically declares at the same time the plurality of living (Bayley; 3, 1960) One of the novelists that keen on writing love as a topic is Khaled Hosseini, an Afghan-born American physician. He is one of the most widely read and beloved novelist in the world. He has told his reader many things about love with Afghan as a background. The Kite Runner published in 2003 by Riverhed Books, Penguin Group division. Although the themes of the novel are about familial relationship, particularly father and son, the price of disloyalty, the inhumanity of rigid class system, and the horrific realities of war, the main theme of Khaled’d writing was LOVE, described trough that universals aspect. In 2007, The Kite Runner was followed by his second novel A Thousand Splendid Suns, which has spent 21 weeks on The New York Times Best Seller list for paperback fiction and 49 weeks on The New York Times Best Seller, list for hardcover fiction (number one for 15 of those weeks). This novel told the reader about two women find comfort and positive side following their self revelation under the endorsement of particular tradition that used to be perceived as the symbol of female subordination of love. The recent Khaled’s novel is And The Mountain Echoed published in 2013 by River Head Books, a member of Penguin Group in New York. Khaled provide the great example of power and love which makes the readers find refreshment. The main story was bout the great affection between motherless siblings. Other kinds of love also provide by Khaled trough the supporting characters and they are also interesting to be discussed. He explores many ways in which family members love, wound, betray, honor, and sacrifice for another; and how often the readers surprised by the actions of those closest to us, at the time that matter most (And The Mountains Echoed cover). REVIEW OF RELATED LITERATURE General Theory of Love In A General Theory of Love by Thomas Lewis, Richard Lannon, and Fari Amini in their book preface explain that love can deliver us to understand our self, and it can also shape our personality. From the beginning till the end of human life, love is not merely centered to the activity we have but also to the life power of the mind, decide our feelings, balancing the bodily rhythms, and reconstruct our brain arrangement. Our identities is fixed and determined by relationship that guaranteed by the body’s physiology (2000, p. viii). Given the open-loop physiology of mammals and their dependence on limbic regulation, attachment interruptions are dangerous. They ought to be highly aversive. And so they are: like a shattered knee or a scratched cornea, relationship ruptures deliver agony. Most people say that no pain is greater than losing someone they love (2000, p. 93). A child enveloped in a particular style of relatedness learns its special intricacies and particular rhythms, as he distills a string of instances into the simpler tenets they exemplify. As he does so, he arrives at an intuitive knowledge of love that forever evades consciousness. He owes the ignorance of his own heart not to repression but to the brains dual memory design. The frustrating illegibility of love's book is, as software makers say of problems with their programs, a feature and not a bug (2000, p. 116). If a child has the right parents, he learns the right principles—that love means protection, caretaking, loyalty, sacrifice. He comes to know it not because he is told, but because his brain automatically narrows crowded confusion into a few regular prototypes (2000, p. 116). Kinds of Love The author of best seller fantasy novel titled Narnia, C.S Lewis, in his book The Four Loves (1960), argued that love is divided into four types. They are affection,friendship, eros and charity. 1. Affection Storge or affection is a love happened between parents with their offspring and also the offspring for parents. In order to explain this term, Lewis provide an example begun from a mother nursing a baby, a bitch or a cat with a basketful of puppies or kittens; all in squeaking, nuzzling heap together; punings, lickings, baby-talk, milk, warmth, the smell of young life(1960, pp. 53-54) Affection, for Lewis, is enlarging far away beyond the relation between mother and her offspring, it happened in animal life, moreover to our own. The feeling get it satisfaction when get together, more than have everything, warm and so comfortable. This is the kind of love that least discriminating, even the unlucky woman or man that have nothing to offer, but the object of this affection is whoever they are; the ugly, the stupid, even the exasperating. It does not need to find out the source of bounding. The brotherhood relation help someone feel better. It happens also between two people that have different thought for instance a clever young man from the university and an old nurse. Lewis has found that affection happened not only between men and dog but amazingly between dog and cat, Gilbert White claimed has found between horse and hen. It is able to proof that even the barrier of species does not able to influence the affection (1960, pp. 54-55). Lewis claimed that affection has its own standard. Its objects must be familiar. The very day and hour when we fell in love or began a new friendship sometimes became the things to point out. But Lewis doubt that we can guess when is the beginning of the affection. When we recognize to guess when affection started is the time when affection has already been going for some time (1960, p. 55). It is the humblest love, it gives but not expect the replies (1960, p. 56). 2. Friendship Philia or friendship is a love among friends-it is a friendship. Borrowing from Aristotle, Lewis explained that friendship is something that quite marginal not a main course in life's banquet; a diversion; something that fills up the chinks at one's time (1960, p. 88). Lewis argued that people can life and breed without friendship, but not without eros and affection, eros present offspring of our own genes, affection completing our life with comfortableness. Biologically, we do not need friendship (1960, p. 88). Lewis also stated that Companionship is the matrix of Friendship. It is often called as Friendship because many people, when they speak of their “friends” mean only their companions. Friendship arises out of mere Companionship when two or more of the companions find that they have in common insight or interest, for instance a common religion, studies, profession and many more. People share their vision then Friendship is born. They stand together in an excellent solitude (1960, p. 96) Lewis argued, friendship is extremely useful, perhaps necessary for survival, to the individual. A Friend will, to be sure, prove himself to be also an ally when alliance becomes necessary; will lend or give when we are in need, nurse us in sickness, stand up for us among our enemies, do what he can for our widows and orphans. But such good offices are not the stuff of Friendship (1960, pp. 101-102). 3. Eros Eros (ἔρως) for Lewis is love in the sense of 'being in love' or 'loving' someone, as the love that belong to lovers. With the consideration that human have similar sexual function with animal, Lewis described Affection as the love in which our experience seems to come closest to that of the animals, but the discussion of eros is not just simple human sexuality. The complex states for being in love happen when we make sexuality as the part of our subject. That sexual experience can occur without Eros, without being